Opinion 2411: Thorectes Mulsant, 1842 (Insecta, Coleoptera, Scarabaeoidea): usage conserved by maintenance of Scarabaeus laevigatus Fabricius, 1798 as type species - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to set aside all previous fixations of type species for the nominal genus Thorectes Mulsant, 1842 prior to the designation of Scarabaeus laevigatus Fabricius, 1798 by López-Colón & Alonso-Zarazaga (2006) which it has accepted as valid.
Keywords: Coleoptera; geotmpid beetles; Geotrupidae; Insecta; Nomenclature; Palaearctica; Scarabaeoidea; Scarabaeus laevigatus; taxonomy; Thorectes